Bipolar transurethral enucleation and resection of the prostate: Whether it is ready to supersede TURP? - Peng Xu; Abai Xu; Binshen Chen; Shaobo Zheng; Yawen Xu; Hulin Li; Haiyan Shen; Chunxiao Liu (Asian Journal of Urology, 2018)
Objective: According to the EAU Guidelines, transurethral resection of the prostate (TURP) has so far still been considered as the gold standard for surgical treatment for patients with obstructing clinical benign prostate hyperplasia (BPH). However, its relatively high rate of complications and postoperative recurrence necessitates further modification and innovation on the surgery technique. We reported the patient outcomes with our technique. Methods: We retrospectively analyzed 52 patients with obstructing clinical BPH who underwent bipolar transurethral enucleation and resection of the prostate (B-TUERP) between March 2015 and September 2015. Pre- and perioperative parameters were obtained from medical charts. Postoperative follow-ups were administrated at 1, 3, 6, 12 and 24 month(s) after surgery, respectively. Results: All the operations were performed successfully with a mean operative time of 43.1 min and an average tissue removal rate of 74.7%. Qmax was significantly improved immediately after surgery, followed by a continuous improvement throughout the follow-ups. Following a steep decrease in mean prostate specific antigen (PSA) and post void residual (PVR) observed within the first half year after surgery, the serum PSA was then maintained at a constant level of 0.61 ng/mL. Temporary urinary retention was found in four cases (7.7%). Stress urinary incontinence occurred in five patients (9.6%), with the condition resolved in 1–2 weeks without extra treatment. Urethral strictures and bladder neck contractures, as the most commonly observed long-term complications, developed in four patients (7.7%). No recurrence was found during 2 years of follow-ups. An improvement in International Index of Erectile Function (IIEF-5) scores was witnessed in 17 patients preoperatively with normal sexual function during the first 6 months after surgery, and sustained throughout the 24-month period. Conclusions: Enucleation reflects an improvement on surgical technique in many ways with a need for surgical equipment that can be broadly accessible in clinical practice. Currently, bipolar resection is a commonly employed procedure in clinical settings, and its similarity shared with bipolar enucleation technique warrants a quick learning of B-TUERP by urologists. Based on these findings, we believe that the substitution of TURP by TUERP as the gold standard for prostate endoscopic procedure can be expected in the future.